A potência do afeto: por uma clínica da gestão - Silva Sobrinho, Jorge Gomes da (2016)
The transition management model in an enterprise is a complex task, which involves a set of variables, often scattered, among them the unpredictable, or those going through the execution of the plan. In family businesses, the unpredictable can be marked by the affective dimension, which is intertwined with the management and the family. The doctoral research this aimed to monitor and systematize a process of change from a centralized model of human resources management (HR) for a distributed and consultative model, a family-owned medium-sized in Pernambuco, welcoming the affective dimension as power Transformative through the creation of daily practices from the same family organizational culture, for construction of the new operating model of HR. In an attempt to systematize this process, a guiding question of the study was built, "How psychology would connect the components of other theoretical and methodological territories, to propose clinical management, which acolhesse and take care of the affective dimension in the transition of such models? " . Adopted a multiple strategy as the theoretical framework, through ergology, schizoanalysis and social psychology from the methodological approach of mapping Deleuze and Guattari (1995), Barros and Kastrup (2009) and Rolnick (2011) in which to intervene is to follow subjectivity production processes. The intervention was carried out in a family business, established in Olinda -PE and activities in the trade of consumer ready food. Participated in the survey, store managers, directors, psychologists, HR management and workers who took turns at different moments of research, divided into four movements: exploratory, depth, action and evaluation. As the new model building mode, we were chosen in the first phase - exploratory - by a documentary analysis of the Handbook on Integration (MI) of new employees and listening directors, psychologists, store managers and HR manager through reflective conversations mounting diagnosis. Even at this stage, the workers were heard through their comments, described the organizational climate survey document held by the HR sector before our research. In the other phases, we have adopted the use of " devices " number to access the experiences of the participants. It was also used the " Field Diary " the researcher as a record of impressions, observations and feelings to participate in the " devices" planned: thematic workshop, clarification meetings, supervision and whells conversations. As a method for analysis of production and diary notes field, we use of mind maps (Novak & Gowin, 1996), built through online applications and remote GOCONQR anda CMAPTOOLS, producing a topography of brands and traits that circulated in rhizome-management through transformative actions. At the end, we understand that clinical mamagement, is positioned as a clinical work, where their activities are aimed at through experiments and inventions, giving passages to implicit and explicit affections in the narrative os Family businesses, through recognition and acceptance of such size, circumscribing new practices based on dialogue between workers, managers and company management.